The Limits of Men’s Identity and the Transgressions of the Patriarchal Order in the Novels Alkar by Dinko Šimunović and Đuka Begović by Ivan Kozarac - Bijelić, Marijana (Poznańskie Studia Slawistyczne, 2025)
The paper is based on a comparative analysis of the novel Alkar by Dinko Šimunović and the novel Đuka Begović by Ivan Kozarac. The existing psychoanalytical analyses of Đuka Begović appear to be insufficient due to the assessment of Šima as an authoritarian father who forbids his son’s pleasure and ignoring the conflict regarding the same woman as reason for patricide. The offered Lacanian analysis of Alkar, on the other hand, fails to capture and explain all the competitive and duplicitous relationships that appear in the text. By expanding the theoretical perspective by engaging René Girard’s mimetic model of desire, it is possible to capture all the mentioned elements. The unsuccessful initiation in Alkar results in the castration of the son, and in Đuka Begović, in patricide, which in both cases causes the sons’ self-expulsion from the social order. In Alkar, the solution is offered in the oral tradition, in the cyclic renewal of the myth, while in Đuka Begović the stabilization of the order is absent.